ANALISIS IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN PEMUDA MELALUI PROGRAM JAMBORE PEMUDA INDONESIA (JPI) DALAM PEMBANGUNAN KEPEMUDAAN DI PROVINSI KALIMANTAN TIMUR - Fachriza Ariyadi (Jurnal Administrative Reform, 2020)
This research is an analysis of the implementation of public policies that specifically focuses and leads to a portrait of the implementation of youth empowerment policies through the Indonesian Youth Jamboree (JPI) Program in youth development in East Kalimantan Province. This study uses a descriptive qualitative methodology. The results showed that the implementation of youth empowerment policies through the JPI program in youth development in East Kalimantan province has generally been going well. Key Word: Policy, Implementation, Indonesian Youth Jamboree (JPI)